COMPREHENSIVE ASSESSMENT OF THE PHYSICAL DEVELOPMENT AND FUNCTIONAL STATUS OF THE CARDIOVASCULAR SYSTEM IN CHILDREN AND ADOLESCENTS INVOLVED IN NATIONAL SPORTS (Academicia Globe: Inderscience Research, 2021)
The physical health of children and adolescents is a basic condition for their all-round and harmonious development, and the basis for the development of intellectual, moral and aesthetic qualities. Physical education is closely linked to children's physical and mental development. The guidelines for kindergarten education clearly require that kindergarten education is age-appropriate and appropriate to the physical and mental development of children and adolescents.